First Kiso pony foal produced via transfer of long-distance shipped fresh embryo to Hokkaido native pony - Reza RAJABI-TOUSTANI; Munkhtuul TSOGTGEREL; Yuanzhi GAO; Canbo LI; Miou SAKATO; Shingo HANEDA; Soon Hon CHEONG; Yasuo NAMBO (The Society for Reproduction and Development, 2023)
Japanese native horses, which consists of 8 breeds, are threatened with extinction. Embryo transfer (ET) is used to reproduce endangered animals in various mammalian species. We aimed to perform ET using native ponies from Kiso and Hokkaido as donors and recipients, respectively. ET operation included long-distance transport of non-cryopreserved embryos from Nagano Prefecture to Hokkaido. Embryos were transported 1500 km over 9 h in a container maintained at 22°C. After transferring two embryos to two recipients, one mare delivered a healthy live foal. These results demonstrated that reciprocal ET with long-distance transportation of fresh embryos between the isolated breeds may allow for the proliferation of Japanese native horses.